Glucose- and Bile Acid-Stimulated Secretion of Gut Hormones in the Isolated Perfused Intestine Is Not Impaired in Diet-Induced Obese Mice - Hunt, Jenna E.; Holst, Jens J.; Jepsen, Sara L. (Frontiers in Endocrinology, 2022)
Purpose Decreased circulating levels of food-intake regulating gut hormones have been observed in type 2 diabetes and obesity. However, it is still unknown if this is due to decreased secretion from the gut mucosal cells or due to extra-intestinal processing of hormones. Methods We measured intestinal hormone content and assessed morphological differences in the intestinal mucosa by histology and immunohistochemistry. Secretion of hormones and absorption of glucose and bile acids (BA) were assessed in isolated perfused mouse intestine. Results GIP (glucose-dependent insulinotropic polypeptide) and SS (somatostatin) contents were higher in the duodenum of control mice (p<0.001, and <0.01). Duodenal GLP-1 (glucagon-like peptide-1) content (p<0.01) and distal ileum PYY content were higher in DIO mice (p<0.05). Villus height in the jejunum, crypt depth and villus height in the ileum were increased in DIO mice (p<0.05 and p=0.001). In the distal ileum of DIO mice more immunoreactive GLP-1 and PYY cells were observed (p= 0.01 and 0.007). There was no difference in the absorption of glucose and bile acids. Distal secretion of SS tended to be higher in DIO mice (p<0.058), whereas no difference was observed for the other hormones in response to glucose or bile acids. Conclusion Our data suggest that differences regarding production and secretion are unlikely to be responsible for altered circulating gut hormone levels in obesity, since enteroendocrine morphology and hormone secretion capacity were largely unaffected in DIO mice.